2013
DOI: 10.3109/10826084.2013.863347
|View full text |Cite
|
Sign up to set email alerts
|

Does It Matter What Friends Think, Say, or Do? The Role of Friends’ Smoking Attitudes and Behavior for Dutch Adolescents’ Smoking Behavior

Abstract: Using stochastic actor-based models for longitudinal network analysis, this study examines the role of friends' smoking attitudes and behavior for Dutch adolescents' smoking behavior in four secondary schools (N = 875). The data were collected in two waves in two small suburban towns under second graders in 2008 to 2009 by means of a standardized questionnaire. Stochastic actor-based models for longitudinal network analysis can control for friendship selection while examining the effect of friends' attitudes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The potential interpretation is that only a few students disagreed with friends smoking and the amount of smokers remained neutral with friends smoking, with less concern for friends smoking status and friends physical health. Besides, smoking initiation was positively associated with having more friends that smoke (Huisman 2014), and previous finding suggested that friends tended to select each other on similar smoking behavior (Voorhees et al 2011), which might explain that the amount of smokers knowing the hazards of smoking still hold the neutral attitude towards friends smoking and may even they agreed with friends smoking.…”
Section: Discussionmentioning
confidence: 77%
“…The potential interpretation is that only a few students disagreed with friends smoking and the amount of smokers remained neutral with friends smoking, with less concern for friends smoking status and friends physical health. Besides, smoking initiation was positively associated with having more friends that smoke (Huisman 2014), and previous finding suggested that friends tended to select each other on similar smoking behavior (Voorhees et al 2011), which might explain that the amount of smokers knowing the hazards of smoking still hold the neutral attitude towards friends smoking and may even they agreed with friends smoking.…”
Section: Discussionmentioning
confidence: 77%
“…Recent studies that utilize developments in social network analysis have found that friendship selection also plays an important role. That is, adolescents tend to befriend peers whose risk behaviors are similar to their own, as has been found in studies of alcohol use (Kiuru et al 2010; Knecht et al 2011; Mercken, Steglich, Knibbe, et al 2012; Sznitman 2013), smoking (de Vries et al 2006; Huisman 2014; Mercken, Steglich, Sinclair, et al 2012), drug use (Poulin et al 2011), delinquent behaviors (Knecht et al 2010), and internalizing behaviors such as depressive symptoms (Goodwin et al 2012; Kiuru et al 2012) and anxiety (Van Zalk et al 2011). Youth also show strong preferences to select friends with similar demographics such as age, race/ethnicity, and gender (Goodreau et al 2009; Moody 2001); attributes that are often correlated with these risk behaviors and so may heighten the similarity in substance use among friends.…”
Section: Introductionmentioning
confidence: 80%
“…They tend to befriend as well as choose to affiliate with peers whose attitudes and behaviors resemble their own on alcohol use [ 25 27 ]. The same socialization pattern applies to smoking [ 28 ] and drug use [ 29 ]. Individuals also tend to overestimate the substance use of their peers, resulting in their own higher levels of substance use [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%